Mechanical properties of flexographic prints / Fleksografinių atspaudų mechaninės savybės - Simona Grigaliūnienė (Mokslas: Lietuvos Ateitis, 2013)
Mechanical properties of paper and flexographic prints madewith different anilox rollers were investigated experimentally.Flexographic prints roughness, breaking force and folding resistancevalues were determined. The results showed that foldingresistance is bigger for machine direction prints than for crossmachine direction prints. Flexographic prints on cardboardsfolding resistance values are different for machine direction andcross machine direction. It was determined that roughness offlexographic prints increases with the amount of ink on aniloxroller. Results were explained by the ink water influence.